2006
DOI: 10.1536/ihj.47.575
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Weaning From a Percutaneous Cardiopulmonary Support System (PCPS) in Patients With Severe Cardiac Failure A Comparative Study in Weaned and Nonweaned Patients

Abstract: SUMMARYThe percutaneous cardiopulmonary support system (PCPS) has been widely accepted for the treatment of patients with severe cardiac failure. This system, which uses Seldinger's method through a percutaneous approach, enables rapid application in emergency situations. However, the indication for deployment and discontinuation of PCPS has not yet been established. We evaluated the results of PCPS use for the treatment of patients with severe cardiac failure and investigated factors that would predict succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Since circulatory deterioration by myocarditis might depend not only on cardiomyocyte injury but also on interstitial edema or fibrosis, 1,2) the mild elevation of the myocardial enzyme in our patient probably reflected relatively mild cardiomyocyte injury and was related to successful treatment with relatively short-term mechanical circulatory support. 31) In conclusion, we reported a case of concurrent FT1D and fulminant viral myocarditis. Viral myocarditis that is accompanied by the onset of FT1D might become clinically evident after correcting ketoacidosis, even when ECG abnormalities are not detected before ketoacidosis treatment.…”
Section: Discussionmentioning
confidence: 69%
“…Since circulatory deterioration by myocarditis might depend not only on cardiomyocyte injury but also on interstitial edema or fibrosis, 1,2) the mild elevation of the myocardial enzyme in our patient probably reflected relatively mild cardiomyocyte injury and was related to successful treatment with relatively short-term mechanical circulatory support. 31) In conclusion, we reported a case of concurrent FT1D and fulminant viral myocarditis. Viral myocarditis that is accompanied by the onset of FT1D might become clinically evident after correcting ketoacidosis, even when ECG abnormalities are not detected before ketoacidosis treatment.…”
Section: Discussionmentioning
confidence: 69%
“…We demonstrated that patients who could be weaned from PCPS required a lower flow rate of PCPS support to maintain systemic circulation at the 24th hour of PCPS treatment. Oshima et al reported that the PCPS flow was reduced 72 h after the initiation of PCPS in patients who could be successfully weaned from PCPS [27]. Their study enrolled patients who experienced severe cardiac failure due to various causes, including postcardiac surgery, pulmonary thrombosis, AMI, and acute myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning from PCPS is often difficult and not always successful due to the complications mentioned above, and therefore, the appropriate discontinuation of PCPS is a critical problem [22,23]. Several reports found that appropriate adjustment of the support flow rate after the initiation of PCPS facilitates the recovery of cardiac function and subsequently contributes to prevent the complications associated with PCPS [24][25][26][27]. To date, there have been no guidelines established for the use of PCPS, nor have methods been established for successful weaning from PCPS.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen patients (1.4%) required PCPS within 48 hours after surgery to maintain hemodynamic stability. The indication for PCPS for severe cardiac failure in our hospital is as follows: 5) peak systolic pressure of less than 80 mmHg and a cardiac index of less than 1.8 L/min/m 2 for more than 30 minutes after correction for hypovolemia, hypoxemia, and acidosis. A decrease in cardiac output unresponsive to intra-aortic balloon pumping (IABP), and patients in whom CPB could not be Vol 48 No 6 discontinued immediately after cardiovascular surgery were also indicated for PCPS.…”
Section: Methodsmentioning
confidence: 99%